Application of lean manufacturing in a peruvian clothing company to reduce the amount of non-conforming products - Cuellar-Valer, Stephanie (2021)
This article describes how Lean Manufacturing tools were applied in a Peruvian textile company. A production management model is proposed whose goal is to reduce the number of non-conforming products in the pants manufacturing line. For this, all information was gathered from the production area of the company under study. With the use of quality tools, the diagnosis of the current situation of the pants line was made, identifying the most significant defects, which were 19.43% of produced units in 2018. It was determined that the main causes of the observed defects refer to non-standardized sewing processes, quality control errors, non-standardized cutting processes, and poor production planning. The application of VSM and SMED allowed the correct standardization of denim pants production, TQM allowed proper control and quality management of the production process, and JIT for optimal production planning.